2014
DOI: 10.3390/ijerph111212429
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical, and Immunohistochemical Investigation of the Damage to Salivary Glands in a Model of Intoxication with Aluminium Citrate

Abstract: Aluminum absorption leads to deposits in several tissues. In this study, we have investigated, to our knowledge for the first time, aluminum deposition in the salivary glands in addition to the resultant cellular changes in the parotid and submandibular salivary glands in a model of chronic intoxication with aluminum citrate in rats. Aluminum deposits were observed in the parotid and submandibular glands. Immunohistochemical evaluation of cytokeratin-18 revealed a decreased expression in the parotid gland with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…In previous studies from our group, we showed Al deposition in the salivary glands [12] and also oxidative stress and morphology impairment after low-dose exposure to Al [22]. However, little is known about the mechanisms related to the effects of chronic and lowdose Al exposure, especially the changes related to molecular impairments.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In previous studies from our group, we showed Al deposition in the salivary glands [12] and also oxidative stress and morphology impairment after low-dose exposure to Al [22]. However, little is known about the mechanisms related to the effects of chronic and lowdose Al exposure, especially the changes related to molecular impairments.…”
Section: Introductionmentioning
confidence: 82%
“…The presence of residual Al in drinking water is one of the most common forms of exposure to the metal [7] and studies indicate that Al can enter the human body through a combination of Al ions with other molecules, forming aluminum salts that can be easily absorbed in the stomach [8,9]. Then, Al is distributed throughout the organism and can affect many organs, such as the cerebellum [10], kidneys [11] and even the salivary glands [12] of animals.…”
Section: Introductionmentioning
confidence: 99%
“…Their presence, and estimated amount, in the swabs certainly warrants a discussion in terms of their potential impact to human health, particularly given the high number of tests that many people are undergoing, which could potentially lead to bioaccumulation of these elements in the body from repeated exposure. The bioaccumulation of aluminium, 28,29 and fluoride 30 are well recognized phenomena, although accumulation is highly dose-dependent. 31,32 Less studied is the bioaccumulation of transition metals in humans.…”
Section: Discussionmentioning
confidence: 99%
“…However, their presence certainly warrants a discussion in terms of their potential impact human health, particularly given the high number of COVID tests that many people are undergoing, which could potentially lead to bioaccumulation from repeated exposure. The bioaccumulation of aluminium [27,28] and fluoride are well-recognized phenomena [29], and are highly dosedependent [30,31]. Less studied is the bioaccumulation of transition metals in humans.…”
Section: Discussionmentioning
confidence: 99%